Aprendizagem e diversão no ensino de química com o uso de jogos didáticos. - Oliveira, Wellyson Cavalcante de. (2014)
One of the major problems faced by teachers of chemistry is the way in which the contents can be worked in order to instigate the student to have a taste for the discipline taught. A portion of the students think the discipline is hard, with memorization of many rules for the understanding of the content. In the face of difficulties, an alternative found is the use of didactic games with content geared toward the teaching of chemistry. This is a fun and contextualized way to revise a subject or even introduce a content differently from the traditional, making use of new teaching methodologies, which approach the content of the reality experienced by students, making the study of chemistry more enjoyable and fun. The present work had as purpose employ didactic games adapted from other already known by the students in order to bring them closer to the instrument used. Three games have been adapted by the insertion of content worked in the classroom, considered difficult by students in order to stimulate the development of critical and engaged thinking. These games were applied in two public schools in João Pessoa city: Olivina Olivia Carneiro da Cunha and Joao Roberto de Souza Borges. In each school were selected third-grade classes. Initially, to test the students previous knowledge about the content considered oral questions were proposed. Then, the games have been applied in these classes. To assess the importance of the use of didactic games as auxiliary material in chemistry lessons, semi-structured questionnaires were applied to both teachers and students. It was subsequently applied a test suggested by one of the teachers. Through the analysis of the results, it can be considered satisfactory the use of didactic games, with their playful and educational dual role as supplementary material in chemistry lessons.